FUNGSI TRADISI GOBA-GOBA MENYAMBUT HARI RAYA IDUL FITRI BAGI MASYARAKAT BIDAR ALAM KECAMATAN SANGIR JUJUAN KABUPATEN SOLOK SELATAN - LUTER, ERWIN - (Pendidikan Sosiologi, 2014)
Natural Bidar Society welcomes Idul Fitri , which is still performed and maintained by the community . Even by modernization and globalization does not make them abandon a tradition that often they do, but keep it up to date . A custom made repeatedly by the people of Bidar Nature indicates that the tradition of an important thing for the people of Bidar Alam , District Sangir Jujuan , Solok Selatan District . Still does tradition - Goba Goba is assumed by society because society has a function for Natural Bidar . Existence of Goba - Goba tradition commemorating the victory of the Islamic religion that is the Eid The formulation of the problem of this study were 1 ) Why Natural Bidar communities still maintain event - Goba Goba 2. What is the function for society Goba Goba - Alam District of Sangir Jujuan Bidar District South Solok While the purpose of the research community to 1. Why Natural Bidar still maintaining event - Goba Goba Goba 2. What is the function for the community - Goba Natural Bidar District of Sangir Jujuan , South Solok. This research approach is qualitative descriptive research to develop the type of problem being investigated. The sampling technique was purposive sampling technique . The technique of collecting data through observation , interview and documentation . This data was analyzed using data analysis : data reduction , data presentation and conclusion. Based on the results it is concluded that : 1 ) Natural Bidar Community .Alasan still maintaining event - Goba Goba welcome Idul Fitri a) the reason the youth village . b ) the reason religious leaders . c ) the reason natural bidar village communities and 2 ) The function Goba - Goba for Community Natural Bidar District of Sangir Jujuan , South Solok a) Function tradition Goba - Goba welcome Idul Fitri b ) Rights and Obligations of Society in a tradition Goba - Goba . c ) Describe the Goba - Goba Tradition Welcoming Idul Fitri